The Demand for and Return to Education When Education Outcomes are Uncertain - Altonji, Joseph G. (Journal of Labor Economics, 1993)
This article treats education as a sequential choice that is made under uncertainty. A simple model is used to explore the effects of ability, high school preparation, preferences for schooling, the borrowing rate, and ex post payoffs to college on the probability of various post-secondary college outcomes and the ex ante return to starting college. The model motivates an empirical method of accounting for uncertainty about educational outcomes and for nonlinearity in the relationship between years of education and earnings when estimating the expected return to the first year of college.